(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
Comparison of values of the binding constant (K) and number of binding sites (n) of methylene blue, ethidium bromide and acridine orange with DNA and RNA has been carried out. It was revealed that values of these parameters do not depend on nucleic acid type. It was shown that in the case of binding of each of these ligands to double-stranded (ds) DNA and ds-RNA the values of K and n are practically similar.